2010
DOI: 10.1109/tie.2009.2028294
|View full text |Cite
|
Sign up to set email alerts
|

Design, Analysis, and Control of a Hybrid Field-Controlled Axial-Flux Permanent-Magnet Motor

Abstract: This paper presents the design, analysis, control, and experimental evaluation of an innovative field-controlled axial-flux surface-mounted permanent-magnet machine. Topology and design equations, as well as an optimized design study, are attained. The machine is investigated in detail using finite-element analysis, and a prototype machine is built. In order to evaluate the new axialflux machine topology, an experimental system setup is devised and discussed. The experimental results of the prototype machine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
61
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(62 citation statements)
references
References 23 publications
1
61
0
Order By: Relevance
“…In order to improve the wide speed range of axial flux PMSM, various special field-weakening methods are proposed and researched [21][22][23][24][25][26][27][28][29][30]. In [21], the rotor pole of the machine adopts a combination of a rare earth magnet (neodymium-iron-bore) and soft laminated iron to reduce the total d-axis reluctance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to improve the wide speed range of axial flux PMSM, various special field-weakening methods are proposed and researched [21][22][23][24][25][26][27][28][29][30]. In [21], the rotor pole of the machine adopts a combination of a rare earth magnet (neodymium-iron-bore) and soft laminated iron to reduce the total d-axis reluctance.…”
Section: Introductionmentioning
confidence: 99%
“…The axial flux PM machine in [22] adopts fractional-slot winding and additional cores enclosing end windings to increase the inductance and then the field weakening capability. In [23,24], a hybrid dual-rotor-single-stator axial machine with a DC field coil located on the stator and a rotor made of alternate PMs and iron teeth is proposed to fulfill a reasonable range of field weakening. This technique allows an easy control of the axial gap flux with DC field current but without any negative effects of current injection.…”
Section: Introductionmentioning
confidence: 99%
“…Lower prices of high-energy permanent magnets and electronics used in motor fabrication also promote utilization of the motors in a wide range of applications [2]. Permanentmagnet motors come in different geometries, among which is a disctype or axial-flux permanent-magnet (AFPM) motor available in various configurations [3][4][5][6][7]. The AFPM motor's high torque-tovolume ratio, excellent efficiency and flat structure are especially suited to military and transport applications, and motivate researchers to develop new approaches to design AFPM machines [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Due to advances in machine design, AFPM machines can have a number of distinct advantages over conventional radial-flux PM machines, such as: a higher torque, better power density and lower noise during operation [16]- [19]. It has also been shown that single air-gap axial flux machines [20]- [23] can generate substantial axial forces which have to be counteracted by shaft bearings.…”
mentioning
confidence: 99%
“…However, this method requires complicated control schemes and efforts in axial force compensation, which may limit the range of the electromagnetic torque. Dual air-gap axial flux machines are used in [19], [24]- [26] where the total axial force is equal to the difference between the two attractive forces of the two air-gaps, and a wider range of field control capability can be achieved. However, these systems have other complications such as the requirement of two power electronic converters to drive the three-phase AC currents [25], [26] or two different converters for the AC currents and for the DC field current drive [19].…”
mentioning
confidence: 99%